Text leads, images and videos follow: the impact of processing paths and input modalities on metaphorical competence in Chinese foreign language learners - Li, Siyun; Zhao, Yang (Frontiers in Language Sciences, 2025)
IntroductionMetaphorical competence is crucial in the accurate and authentic use of a second language. Processing paths (rational processing verses contextual guessing) and input modalities (unimodal verses multimodal) are major factors that may influence learners' metaphorical acquisition. This study explored how these variables relate to influence Chinese foreign language (CFL) learners' metaphorical competence.MethodsAdvanced CFL participants (N = 60) were divided into four groups using combinations of various processing paths (rational processing and contextual guessing) and input modalities (unimodal and multimodal), and subsequently completed three posttests. The data were subjected to correlation analysis using SPSS software.ResultsRational processing excelled in metaphor comprehension competence (MCC), particularly with unimodal input, although metaphor production competence (MPC) showed an overall decline, especially in multimodal conditions; the rational processing path significantly outperformed the contextual guessing path in the immediate posttest in the three delayed posttests, but the effect diminished over time; Using the rational processing path, test times significantly affected MCC, whereas, MPC was affected by input modality and test times; Using the contextual guessing path, test times significantly affected MCC; With unimodal input, processing paths and test times significantly affected MCC, whereas processing paths affected MPC; With multimodal input, test times significantly affected MCC. MCC increased with time, whereas MPC decreased.DiscussionThis research confirms the applicability of Depth-of-processing Theory, Cognitive Load Theory, and spaced learning strategies in enhancing metaphorical competence through different processing paths and input modalities, thereby expanding their relevance in the domain of CFL acquisition.